PENGGUNAAN MEDIA GAMBAR PADA KEMAMPUAN MENULIS CERITA PENDEK DI SMPN 22 MATARAM - Syaiful Bahri (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
Some students find difficulty in writing activity although only write one paragraph. Hence, it needs one media to make easier in this problem. The aim of this research to describe the students’ progress in writing a short story using a picture at SMPN 22 Mataram in 2014-2015. The method of this research is blending which combine the qualitative and descriptive. The write conducted this research in 3 cycles. From the result we can see that in the first cycle, there are 9,5% students have been a success in this activity, for the second cycle, there are 50% progress and the third cycle all the students can pass or qualified in doing writing activity. It means that this research can reach the target of the learning process